A pH‐Responsive Hydrogel Based on a Tumor‐Targeting Mesoporous Silica Nanocomposite for Sustained Cancer Labeling and Therapy. Issue 18 (22nd July 2016) - Chen, Xin; Liu, Zhongning
Abstract : A facile strategy is presented to synthesize hyaluronic acid (HA) and a fluorescein isothiocyanate (FITC)‐conjugated mesoporous silica nanocomposite (MSN) with multiple functions of fluorescence, tumor‐cell targeting, pH‐triggered gelation, and enzyme‐responsive drug release. This injectable nanocomposite is able to indicate the entire tumor location and provides a microenvironment with rich anticancer drugs in and around tumor tissue for a long time, to avoid recrudescence. In this design, the mesoporous silica serves as the drug container, the FITC serves as a fluorescent probe, and the anchored HA plays multiple roles as drug‐release cap, tumor‐targeting points, and responsive gel matrix. Owing to the specific affinity between the HA on MSNs and the CD44 antigen over‐expressed on tumor cells, the MSNs can selectively attach to tumor cells. The nanocomposites then exploit the pH‐responsive interactions (hydrogen bonds) among the HA to self‐assemble in situ into a hydrogel around the tumor tissue. The resulting hydrogel gradually releases its payload (doxorubicin, anticancer drugs)‐loaded MSNs upon HA degradation in the presence of hyaluronidase‐1 (Hyal‐1), followed by endocytosis and intracellular drug release. All these properties have distinct benefits for tumor treatment, demonstrating that this device is a promising candidate for oncotherapy applications. Abstract : A fluorescent mesoporous silica nanoconjugate end‐capped with hyaluronic acid is developed, which displays great potential for tumor targeting, labeling, effective particle‐to‐hydrogel transformation in tumor environment, and controlled drug release in response to specific enzymes in tumor cells.